DETERMINATION OF TH DYNAMICS OF THE FIELD AREA WITH FOOD SUPPORTUSING REMOTE SENSING IN SOLOK DISTRICT - Teguh Trivo Maulana; Fitriana Syahar (International Remote Sensing Applied Journal, 2022)
The availability of carrying capacity of food in an area is closely related to the availability of sufficient agricultural rice fields, from both sides they are very mutually supportive, so if the area of agricultural land is in an area, the availability of food in the area will also help reduce this problem. will have an impact on the food-carrying capacity of the people in the region. This study uses a quantitative descriptive approach using a supervised classification method using the SNI 7645 Classification. The data required are Landsat images from 2000, 2010 and 2020 . The data obtained from the results of image data processing is the occurrence of changes in the area of rice fields in Solok Regency in 2000, 2010 and 2020, where in 2000 the area of rice fields was 90,344, in 2010 the area of rice fields again was 80,452Ha, and in 2020 the area of rice fields continues to decrease to 75,750 Ha.